Analisa Pemahaman Masyarakat terhadap Ekonomi Syariah - Nuriyah Nasution; Rahmayati (Syntax Literate, 2023)
The lack of academic or professional outreach from related institutions, the existence of Islamic Financial Institutions (LKS) does not necessarily play an active role. Not to mention the lack of knowledge of Islamic economics in society, which encourages public perception that the Islamic and Western economic systems are equal. Even though there are many LKS in the area, people's understanding of Islamic economics is still very minimal. This case study was carried out partly because of the concern of the residents of Pangulah Selatan hamlet. The purpose of this research is to increase public awareness and understanding of the fundamental ideas of Islamic economics, support local community economic development, and protect against usury debt (including loan sharks). The author's research methodology is qualitative.